Medienpädagogische Qualifikation für Lehrkräfte - Herzig, Bardo; Martin, A. (Medien – Bildung - Schule, Dokumentation der ersten Netzwerktagung Medienkompetenz Sachsen-Anhalt, Halle (Saale), 19. und 20. September 2011)

Wenn der Konzertsaal zur Kirche wird. Mendelssohn Bartholdy, Schleiermacher und die Wiederaufführung der Matthäuspassion 1829 - Janus, Richard (Musik in Religion - Religion in Musik)

Invokavit: Was ist Glück? - Janus, Richard (...und den Mond als Licht für die Nacht. Andachten zur Nacht im Kirchenjahr)

Bernd Zymner: 100 Jahre Auferstehungskirche in Brakel. "eine neue, völlig eigene Kirche, die evangelischen Begriffen entspricht, Brakel 2012 - Janus, Richard (Paderborner Historische Mitteilungen)

Template-based question answering over RDF data - Unger, Christina; Bühmann, Lorenz; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille; Gerber, Daniel; Cimiano, Philipp (Proceedings of the 21st World Wide Web Conference 2012, WWW 2012, Lyon, France, April 16-20, 2012)

Konzeption eines Regelungssystems zur gezielten Beeinflussung der Fahrdynamik in Unfallsituationen - Salfeld, Maike

A fully digital polar modulator for switch mode RF power amplifier - Ostrovskyy, Philip; Scheytt, Christoph; Lee, SungJun; Park, BongHyuk; Jung, JaeHo (Proc. IEEE Int Circuits and Systems (ISCAS) Symp)
In this paper, a novel fully digital modulator for a switch mode power amplifier (SMPA) is presented. The modulator converts the input baseband amplitude and phase signals into a two-level pulse train for driving an RF SMPA. The simulation results demonstrated a proof of the concept. The proposed architecture is analyzed in terms of accuracy by measuring EVM. The impact of the modulator parameters on the SMPA performance is investigated and corresponding results are shown. The modulator was simulated with a 20 MHz LTE signal.

Low-power 20-Gb/s SiGe BiCMOS driver with 2.5 V output swing - Sedighi, Behnam; Ostrovskyy, Philip; Scheytt, Christoph; Stille, Karl Stephan Christian; Böcker, Joachim (Microwave Symposium Digest (MTT), 2012 IEEE MTT-S International)
this paper investigates low-power design of high-speed and high-swing electronic driver circuits. A method to estimate and optimize the power consumption of such driver ICs is presented. A 20-Gb/s driver circuit is fabricated in 0.25 µm SiGe BiCMOS process and an output swing of 2.5 V pp is measured. The driver consumes 0.75 W from 5 V supply.

Balanced homodyne detection of optical quantum states at audio-band frequencies and below - Stefszky, Michael; Mow-Lowry, C M; Chua, S S Y; Shaddock, D A; Buchler, B C; Vahlbruch, H; Khalaidovski, A; Schnabel, R; Lam, P K; McClelland, D E (Classical and Quantum Gravity)

Leveraging Social Network Data for Analytical CRM Strategies --- The Introduction of Social BI - Rosemann, Michael; Eggert, Mathias; Voigt, Matthias; Beverungen, Daniel (Proceedings of the 20$^{th}$ European Conference on Information Systems)

Hybrid functionals and GW approximation in the FLAPW method - Friedrich, Christoph; Betzinger, Markus; Schlipf, Martin; Blügel, Stefan; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
We present recent advances in numerical implementations of hybrid functionals and the GW approximation within the full-potential linearized augmented-plane-wave (FLAPW) method. The former is an approximation for the exchange–correlation contribution to the total energy functional in density-functional theory, and the latter is an approximation for the electronic self-energy in the framework of many-body perturbation theory. All implementations employ the mixed product basis, which has evolved into a versatile basis for the products of wave functions, describing the incoming and outgoing states of an electron that is scattered by interacting with another electron. It can thus be used for representing the nonlocal potential in hybrid functionals as well as the screened interaction and related quantities in GW calculations. In particular, the six-dimensional space integrals of the Hamiltonian exchange matrix elements (and exchange self-energy) decompose into sums over vector–matrix–vector products, which can be evaluated easily. The correlation part of the GW self-energy, which contains a time or frequency dependence, is calculated on the imaginary frequency axis with a subsequent analytic continuation to the real axis or, alternatively, by a direct frequency convolution of the Green function G and the dynamically screened Coulomb interaction W along a contour integration path that avoids the poles of the Green function. Hybrid-functional and GW calculations are notoriously computationally expensive. We present a number of tricks that reduce the computational cost considerably, including the use of spatial and time-reversal symmetries, modifications of the mixed product basis with the aim to optimize it for the correlation self-energy and another modification that makes the Coulomb matrix sparse, analytic expansions of the interaction potentials around the point of divergence at k=0, and a nested density and density-matrix convergence scheme for hybrid-functional calculations. We show CPU timings for prototype semiconductors and illustrative results for GdN and ZnO.

Strategy Planning of Collaborative Humanoid Soccer Robots based on Principle Solution - Low, Cheng; Aldemir, Mustafa; Aziz, Norheliena; Dumitrescu, Roman; Anacker, Harald (Proceedings of the 1st German-Malaysian Workshop, Hannover, 27. - 29. Jun. 2012)

Graph Transformation - 6th International Conference, ICGT 2012, Bremen, Germany, September 24-29, 2012, Proceedings

Energy Efficient Clustering using a Wake-up Receiver - Blanckenstein, Johannes; Klaue, Jirka; Karl, Holger (European Wireless 2012 - 18th European Conference 2012, April 18-20, 2012, Poznan, Poland.)

Efficiency of On-Path and Off-Path Caching Strategies in Information Centric Networks - Dräxler, Martin; Karl, Holger (2012 IEEE International Conference on Green Computing and Communications, Conference on Internet of Things, and Conference on Cyber, Physical and Social Computing, GreenCom/iThings/CPSCom 2012, Besancon, France, November 20-23, 2012)

Quantization techniques for accurate soft message combining - Volkhausen, Tobias; Schinköthe, Kai; Karl, Holger (2012 IEEE Wireless Communications and Networking Conference, WCNC 2012, Paris, France, April 1-4, 2012)

Efficient cooperative relaying in wireless multi-hop networks with commodity WiFi hardware - Volkhausen, Tobias; Dridger, Kornelius; S. Lichte, Hermann; Karl, Holger (10th International Symposium on Modeling and Optimization in Mobile, Ad Hoc and Wireless Networks (WiOpt), Paderborn, Germany, May 14-18, 2012)

Model-Based Testing: Achievements and Future Challenges - Mlynarski, Michael; Güldali, Baris; Weißleder, Stephan; Engels, Gregor (Advances in Computers)
Software systems are part of our everyday life and they become more complex day by day. The ever-growing complexity of software and high quality requirements pose tough challenges to quality assurance. The quality of a software system can be measured by software testing. However, if manually done, testing is a time-consuming and error-prone task. Especially test case design and test execution are the most cost-intensive activities in testing. In the previous 20 years, many automation tools have been introduced for automating test execution by using test scripts. However, the effort for creating and maintaining test scripts remains. Model-based testing (MBT) aims at improving this part by systematizing and automating the test case design. Thereby, test cases or automatable test scripts can be generated systematically from test models. MBT is already known for several years, but it currently gains a great momentum due to advanced tool support and innovative methodological approaches. This chapter aims at giving an overview of MBT and summarizes recent achievements in MBT. Experiences with using the MBT approach are illustrated by reporting on some success stories. Finally, open issues and future research challenges are discussed.

Growth of cubic GaN on 3C–SiC/Si (001) nanostructures - Kemper, R.M.; Hiller, L.; Stauden, T.; Pezoldt, J.; Duschik, K.; Niendorf, T.; Maier, H.J.; Meertens, D.; Tillmann, K.; As, D.J.; Lindner, Jörg (Journal of Crystal Growth)
We report on the molecular beam epitaxy growth of cubic GaN on 3C–SiC (001) nanostructures. Transmission electron microscopy (TEM) studies show phase-pure cubic GaN crystals with a low defect density on top of the post shaped 3C–SiC nanostructures and GaN grown on their sidewalls, which is dominated by {111} planar defects. The nanostructures, aligned parallel and perpendicular to the [110] directions of the substrate, are located in anti-phase domains of the 3C–SiC/Si (001) substrate. These anti-phase domains strongly influence the optimum growth of GaN layers in these regions. TEM measurements demonstrate a different stacking fault density in the cubic GaN epilayer in these areas.

Self-Organized Nanostructure Formation for Anti-Reflection Glass Surfaces - Achtelik, Jörn; Kemper, Ricarda M.; Sievers, Werner; Lindner, Jörg (MRS Proceedings)
Two methods to create biomimetic anti-reflection nanostructures in ordinary glass microscope object slides are presented. One technique is based on a nanosphere lithography process combined with physical vapour deposition of nickel and reactive ion etching (RIE). The other uses plasma induced dewetting of a smooth nickel surface. The amount of reflected light was measured and a method to simulate the reflectivity from an atomic force microscopy (AFM) topography scan of the glass surface is presented. The reflectivity for visible light at normal incidence was reduced to 20-50 % of the original value with both methods and the simulation gives results in good agreement to the measurement.